2009
DOI: 10.4067/s0716-97602009000200013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate water potential in root growth of Agave salmiana Otto ex Salm-Dyck seedlings

Abstract: The objective of this study was to test the hypothesis that root of maguey (Agave salmiana Otto ex Salm-Dyck) seedlings reacts during the first 24 h to low substrate water potential (Ψ W), by anatomical modifications. Three-4 cm root length seedlings were planted in vermiculite for 24 h at Ψ W between-0.03 and-2.35 MPa. Root dimensions, proline content and anatomy were evaluated. Substrate Ψ W between-0.65 and-2.35 MPa did not significantly affect longitudinal root growth. However, proline content significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
(7 reference statements)
2
12
0
Order By: Relevance
“…The increase of cortical parenchyma cells number in the plants subjected to severe water deficit indicated that root tissue dehydration accelerates cellular division. On the other hand, the increased stele/ root cross-section area under moderate drought stress, suggest an important role for the stele, probably in water transport by helping to retain root water under drought, rather than in water uptake under drought [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of cortical parenchyma cells number in the plants subjected to severe water deficit indicated that root tissue dehydration accelerates cellular division. On the other hand, the increased stele/ root cross-section area under moderate drought stress, suggest an important role for the stele, probably in water transport by helping to retain root water under drought, rather than in water uptake under drought [28].…”
Section: Discussionmentioning
confidence: 99%
“…The root and cortex thickness are generally smaller in stressed plants. A recent study showed that root cortex thickness was reduced in sensitive varieties of rice subjected to water deficit [28]. Cortical parenchyma might serve as a storage area of nutrients and water [29].…”
Section: Discussionmentioning
confidence: 99%
“…Three different vermiculite Ψ W (-0.03, -1.0 and -1.5 MPa) were obtained by mixing 100 g dry vermiculite with 170, 16 or 11 mL distilled water (w:v) in polyethylene bags. These were sealed for 48 h before the start of the assay, according to Peña-Valdivia and Sánchez-Urdaneta [6], after which time a vermiculite sample was incubated in a psychrometric chamber (Wescor C-52, Inc, Utha, USA) for 4 h, and its Ψ W was subsequently determined by connecting the chambers to a microvoltmeter (Wescor HR-33 T, Inc, Utha, USA) operated in the dew-point mode.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that after germination under optimal conditions, seedlings of A. salmiana can grow on a substrate with a water potential (Ψ W ) of -2.5 MPa [6] and young and adult plants of A. salmiana and A. angustifolia ssp. tequilana maintain active photosynthetic pathway after six months without water, and even throughout the whole dry season [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, an alteration of the temporal pattern of xylem differentiation was observed in roots of soybean (Glycine max) plants upon saline stress, with a delay in primary xylem differentiation and a precocious formation of secondary xylem (Hilal et al, 1998). Moreover, significant anatomical changes were observed to occur in roots of Agave salmiana under water stress, among them a reduction of vessel number and an increase of xylem diameter and wall thickness (Peña-Valdivia and Sánchez-Urdaneta, 2009). The rearrangement of root vascular tissues has also been reported to occur as a defense reaction against pathogen invasion, such as the regeneration of xylem vessels observed in a Fusarium spp.…”
mentioning
confidence: 95%